Middlemarch - Eliot, George, 1819-1880; Edited by Ashton, Rosemary (London Penguin Books, 1994)
Part of Alma Classics Evergreen series of popular classics, Middlemarch is a literary landmark in its groundbreaking approach, as well as a priceless document of its age. This edition is thoroughly edited and extensively annotated and includes pictures and a comprehensive section on Eliot's life and works
Include Notes
Keywords: England -- Young women -- City and town life